Identifying the cultural heritage of patients during clinical handover and in hospital medical records. Issue 5 (18th January 2019) - Morgan, David JR; Harris, Tania; Gidgup, Ron; Whitely, Martin
Abstract: Objective: To examine the frequency of and rationale for hospital doctors mentioning a patient's cultural heritage (ethnicity, national heritage, religion) during medical handovers and in medical records. Design: Four‐phase observational study, including the covert observation of clinical handovers in an acute care unit (ACU) and analysis of electronic medical records (EMRs) of ACU patients after their discharge to ward‐based care. Setting, participants: 1018 patients and the doctors who cared for them at a tertiary hospital in Western Australia, May 2016 – February 2018. Main outcome measure: References to patients' cultural heritage by ACU doctors during clinical handover (written or verbal) and by ward‐based doctors in hospital EMRs (written only), by geographic ethnic–national group. Results: In 2727 ACU clinical handovers of 1018 patients, 142 cultural heritage identifications were made (ethnicity, 84; nationality, 41; religion, 17); the rate was highest for Aboriginal patients (370 [95% CI, 293–460] identifications per 1000 handovers). 14 505 EMR pages were reviewed; 380 cultural heritage identifications (ethnicity, 257; nationality, 119; religion, 4) were recorded. A rationale for identification was documented for 25 of 142 patients (18%) whose ethnic–national background was mentioned during handover or in their EMR. Multivariate analysis (adjusted for demographic, socio‐economic and medical factors) indicated that being an Aboriginal Australian was the most significant factor for identifying ethnic–national background (handovers: adjusted odds ratio [aOR], 21.7; 95% CI, 7.94–59.4; hospital EMRs: aOR, 13.6; 95% CI, 5.03–36.5). 44 of 75 respondents to a post‐study survey (59%) were aware that Aboriginal heritage was mentioned more frequently than other cultural backgrounds. Conclusions: Explicitly mentioning the cultural heritage of patients is inconsistent and seldom explained. After adjusting for other factors, Aboriginal patients were significantly more likely to be identified than patients with other backgrounds.